Application Research of High-intensity mixing Technology and Equipment in a Concentrator of Jiama, Tibet - Wazhuoma Da; Zilong Liu; Zhao Xie; Lei Li; Xikangzhuo Yi; Xizhen Yuan (Kuangchan zonghe liyong, 2023)
In order to solve the shortage of shear capacity of the conventional axial-flow agitator, a concentrator of Jiama in Tibet has adopted a new type of high-intensity mixing technology and equipment. The mineral particles in the pulp and flotation agents can be fully contacted and mixed. The laboratory comparison test shows that appropriately increasing the speed of stirring and adjusting slurry before flotation and appropriately extending the time of stirring and adjusting slurry before flotation can increase the flotation recovery rate within a certain range. The comparison of production indexes shows that the recovery rates of Cu, Au, Ag and Mo with the equipment are 0.53%, 3.92%, 1.04% and 6.25% higher than those without the equipment when the two series treat the same ore with the same concentration, fineness, reagents system and process. The equipment strengthens the shearing effect of impeller, increases the chance of collision between reagents and mineral particles, gives full play to the effect of reagents and improves the beneficiation index.